BILINGUAL EDUCATION IN MOZAMBIQUE: : ANALYSIS OF EDUCATIONAL POLICIES AND THEIR IMPLEMENTATION IN PRIMARY EDUCATION (Interdisciplinary Studies Journal, 2026)
This article analyzes bilingual education in Mozambique as a strategy adopted by the State to address the country's linguistic diversity and the learning difficulties faced by children whose mother tongue is not Portuguese. The study examines educational policies related to bilingual education and how they guide its implementation in the first and second cycles of primary education. Methodologically, this is a qualitative documentary research study based on the analysis of laws, strategic plans, and curricular guidelines in the education sector. The results indicate that, although bilingual education is well established at the policy and regulatory level, its expansion faces challenges related to managing linguistic diversity in schools, teacher training, and the production of teaching materials. In certain social groups, resistance persists due to the exclusive valorization of Portuguese as a factor of social mobility. This situation may exacerbate educational inequalities if integrated language policies and awareness-raising strategies are not implemented to promote a more balanced understanding of the role of Mozambican languages in the educational process.
Keywords: Bilingual Education; National Languages; Language Policy; Mozambique